ANALISA BUFFER DALAM SISTEM INFORMASI GEOGRAFIS UNTUK PERENCANAAN RUANG KAWASAN - Wafirul Aqli (Universitas Negeri Yogyakarta, 2010)
ABSTRACTOn the scale of area or region in spatial planning, it is important to evaluate andto predict the new spatial plan and policy, whether it is effective or not to beimplemented. It is intended that the results of the spatial planning in scale of area orregion, can be optimized to accommodate the needs. Geographical InformationSystem as a computerized instrument of planning is pretty decent to be used for thosestages of planning (evaluation and prediction). More specifically one of its analysisfeature, buffer analysis, is capable to measure the effectiveness of the presence ofpublic facilities –for example- in terms of coverage/distribution of services (in thecontext of evaluation stage). In addition, buffer analysis also capable to predictwhether the spatial policies and its physical implementation possible to be place inaccordance with the goal of the planning.Keyword: Geographical Information System, Buffer Analysis, Spatial Planning.